Handbook of research on waste management techniques for sustainability - Akkucuk, Ulas 1975- (Advances in environmental engineering and green technologies (AEEGT) book series, 2016)
This book explores the topic of sustainable development in an era where domestic and municipal waste is becoming a concern for both human and environmental health, highlighting a number of topics relating to pollution, green initiatives, and waste reduction in both the public and private sector.